Soil constraints and recommendations for improving major farming in Vinh Long province, Vietnam - Minh, V Q; Thanh, Vu P; Hung, T V; Dang, P C; Phat, P N; Vu, L H; Tuan, T (Plant Science Today, 2025)
This study aims to assess the potential of soil and its constraints for production to meet economic needs and diversify types of crop models of Vinh Long province in the Vietnamese Mekong Delta region. Identifying the main constraints of the soil is the basis for reasonable land arrangement and proposing measures to maintain and improve the soil characteristics suitable for each crop type and purpose of use. The study used survey methods, interviewed farmers about the current farming situation and collected soil samples to analyze physical and chemical properties. Research results show that in Vinh Long, for three main crops, namely rice, fruit trees (grapefruit trees) and sweet potatoes, the primary constraints are a potential and active acid sulfate and low pH soil. In addition, Al toxicity causes phosphorus fixation, the exchangeable K content is low and the organic matter is only moderate. These limitations have affected crop productivity, especially for fruit trees. The research results also recommended improving soil properties suitable for the cultivation of major crops, including controlling the water level so as not to oxidize the sulfidic material to active acid sulfate soils, draining the water at the beginning of the season rain to leach the toxicity in the soil and need to fertilize with nitrogen, phosphorus and potassium supplements for a long time, divided into several times of application.